Moral Education in the Digital Age : Building Character and Instilling Faith Values in the Era of Technological Advancement - Maslahah, Hanum Mir'atul (Proceeding International Conference on Education, 2023)
The digital age has had a significant impact on various aspects of life, including education and individual character formation. Technological advances allow easier access to information and knowledge from around the world, connect people from various regions, and influence student behavior and morals. However, this impact has positive and negative sides. Students can increase their knowledge through technology but can also be distracted by negative content. Management of technology use is key to exploiting positive potential while avoiding negative impacts. Character education and religious values are important in facing these changing times, with the role of teachers and parents in forming good morals in the younger generation. Online content selection and positive character teaching are required. Education in the digital era also emphasizes increasing individual abilities, balanced with the measurable use of technology. Finally, instilling the values of faith and good morals can be done with various strategies, such as exemplary stories, the use of technology in learning, and the habit of positive behavior, all of which aim to create individuals with character.